Looking for trustworthy answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Get quick and reliable solutions to your questions from a community of experienced experts on our platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
To solve the inequality [tex]\((x-4)(x+2) > 7\)[/tex], we need to proceed by manipulating it into a form that we can analyze more conveniently. Here are the steps:
1. Set up the inequality:
[tex]\[ (x-4)(x+2) > 7 \][/tex]
2. Isolate the quadratic expression:
Subtract 7 from both sides to focus on finding the critical points where the expression equals zero:
[tex]\[ (x-4)(x+2) - 7 > 0 \][/tex]
3. Factor the quadratic expression:
Let's set the expression equal to zero to find the critical points where changes might occur in the inequality:
[tex]\[ (x-4)(x+2) - 7 = 0 \][/tex]
This can be expanded to:
[tex]\[ x^2 - 4x + 2x - 8 = 7 \][/tex]
Combine like terms:
[tex]\[ x^2 - 2x - 8 = 7 \][/tex]
Then move 7 to the left side:
[tex]\[ x^2 - 2x - 15 = 0 \][/tex]
4. Solve the quadratic equation:
Use the quadratic formula [tex]\(x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\)[/tex], where [tex]\(a=1\)[/tex], [tex]\(b=-2\)[/tex], and [tex]\(c=-15\)[/tex]:
[tex]\[ x = \frac{-(-2) \pm \sqrt{(-2)^2 - 4(1)(-15)}}{2(1)} \][/tex]
[tex]\[ x = \frac{2 \pm \sqrt{4 + 60}}{2} \][/tex]
[tex]\[ x = \frac{2 \pm \sqrt{64}}{2} \][/tex]
[tex]\[ x = \frac{2 \pm 8}{2} \][/tex]
Hence, the solutions are:
[tex]\[ x = \frac{10}{2} = 5 \quad \text{and} \quad x = \frac{-6}{2} = -3 \][/tex]
5. Determine the intervals for testing:
The quadratic equation [tex]\(x^2 - 2x - 15 = 0\)[/tex] has the roots [tex]\(x = -3\)[/tex] and [tex]\(x = 5\)[/tex]. These points divide the number line into three intervals: [tex]\((- \infty, -3)\)[/tex], [tex]\((-3, 5)\)[/tex], and [tex]\((5, \infty)\)[/tex].
6. Test the intervals:
To find where the inequality [tex]\((x-4)(x+2) > 7\)[/tex] holds true, we test points within these intervals:
- For the interval [tex]\((- \infty, -3)\)[/tex], pick [tex]\(x = -4\)[/tex]:
[tex]\[ (x-4)(x+2) - 7 = (-4-4)(-4+2) - 7 = (-8)(-2) - 7 = 16 - 7 = 9 > 0 \][/tex]
This is true, so the inequality holds in [tex]\((- \infty, -3)\)[/tex].
- For the interval [tex]\((-3, 5)\)[/tex], pick [tex]\(x = 0\)[/tex]:
[tex]\[ (x-4)(x+2) - 7 = (0-4)(0+2) - 7 = (-4)(2) - 7 = -8 - 7 = -15 < 0 \][/tex]
This is false, so the inequality does not hold in [tex]\((-3, 5)\)[/tex].
- For the interval [tex]\((5, \infty)\)[/tex], pick [tex]\(x = 6\)[/tex]:
[tex]\[ (x-4)(x+2) - 7 = (6-4)(6+2) - 7 = (2)(8) - 7 = 16 - 7 = 9 > 0 \][/tex]
This is true, so the inequality holds in [tex]\((5, \infty)\)[/tex].
Therefore, the solution for [tex]\((x-4)(x+2) > 7\)[/tex] is:
[tex]\[ (-\infty < x < -3) \cup (5 < x < \infty) \][/tex]
1. Set up the inequality:
[tex]\[ (x-4)(x+2) > 7 \][/tex]
2. Isolate the quadratic expression:
Subtract 7 from both sides to focus on finding the critical points where the expression equals zero:
[tex]\[ (x-4)(x+2) - 7 > 0 \][/tex]
3. Factor the quadratic expression:
Let's set the expression equal to zero to find the critical points where changes might occur in the inequality:
[tex]\[ (x-4)(x+2) - 7 = 0 \][/tex]
This can be expanded to:
[tex]\[ x^2 - 4x + 2x - 8 = 7 \][/tex]
Combine like terms:
[tex]\[ x^2 - 2x - 8 = 7 \][/tex]
Then move 7 to the left side:
[tex]\[ x^2 - 2x - 15 = 0 \][/tex]
4. Solve the quadratic equation:
Use the quadratic formula [tex]\(x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\)[/tex], where [tex]\(a=1\)[/tex], [tex]\(b=-2\)[/tex], and [tex]\(c=-15\)[/tex]:
[tex]\[ x = \frac{-(-2) \pm \sqrt{(-2)^2 - 4(1)(-15)}}{2(1)} \][/tex]
[tex]\[ x = \frac{2 \pm \sqrt{4 + 60}}{2} \][/tex]
[tex]\[ x = \frac{2 \pm \sqrt{64}}{2} \][/tex]
[tex]\[ x = \frac{2 \pm 8}{2} \][/tex]
Hence, the solutions are:
[tex]\[ x = \frac{10}{2} = 5 \quad \text{and} \quad x = \frac{-6}{2} = -3 \][/tex]
5. Determine the intervals for testing:
The quadratic equation [tex]\(x^2 - 2x - 15 = 0\)[/tex] has the roots [tex]\(x = -3\)[/tex] and [tex]\(x = 5\)[/tex]. These points divide the number line into three intervals: [tex]\((- \infty, -3)\)[/tex], [tex]\((-3, 5)\)[/tex], and [tex]\((5, \infty)\)[/tex].
6. Test the intervals:
To find where the inequality [tex]\((x-4)(x+2) > 7\)[/tex] holds true, we test points within these intervals:
- For the interval [tex]\((- \infty, -3)\)[/tex], pick [tex]\(x = -4\)[/tex]:
[tex]\[ (x-4)(x+2) - 7 = (-4-4)(-4+2) - 7 = (-8)(-2) - 7 = 16 - 7 = 9 > 0 \][/tex]
This is true, so the inequality holds in [tex]\((- \infty, -3)\)[/tex].
- For the interval [tex]\((-3, 5)\)[/tex], pick [tex]\(x = 0\)[/tex]:
[tex]\[ (x-4)(x+2) - 7 = (0-4)(0+2) - 7 = (-4)(2) - 7 = -8 - 7 = -15 < 0 \][/tex]
This is false, so the inequality does not hold in [tex]\((-3, 5)\)[/tex].
- For the interval [tex]\((5, \infty)\)[/tex], pick [tex]\(x = 6\)[/tex]:
[tex]\[ (x-4)(x+2) - 7 = (6-4)(6+2) - 7 = (2)(8) - 7 = 16 - 7 = 9 > 0 \][/tex]
This is true, so the inequality holds in [tex]\((5, \infty)\)[/tex].
Therefore, the solution for [tex]\((x-4)(x+2) > 7\)[/tex] is:
[tex]\[ (-\infty < x < -3) \cup (5 < x < \infty) \][/tex]
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.